Ars poetica I classici greci e latini nell'opera di Giorgio Bassani - Claudio Cazzola (Moderna/Comparata, 2018)
Despite the many studies on the author and the wealth of data on his academic education, relatively little was known of the high school years of Giorgio Bassani and the decisive encounters during those years. This book, rich in data and discoveries, traces precisely that dark area, identifies in Francesco Viviani the first of the Masters who, well beyond the period spent in the classrooms, would have exerted a profound influence on the future writer. The Greek and Latin texts read in those distant times are among those indicated by Professor Guzzo in Dietro la porta (Behind the Door), confirming the profoundly educational role that classical culture had had for the genesis of the ethical commitment and the search for truth which is the basis of all the Bassanian writing. Catullo, Alceo and especially Orazio will become for Bassani, according to Claudio Cazzola's analysis, examples to be emulated with refined allusive art, suggesting a compositional method that sees in a tireless limae labor the secret and authentic justification for the existence not only of Ferrara novel but also of its author.